CAx für Ingenieure : Eine praxisbezogene Einführung /: Eine praxisbezogene Einführung. (2018) - Vajna, Sándor; Weber, Christian; Zeman, Klaus; Hehenberger, Peter; Gerhard, Detlef; Wartzack, Sandro
No abstract available